Exploring surface chemistry and electrical performance of zinc tin oxide thin films with controlling elemental composition grown by atomic layer deposition - Lim, Dong Hyun; Choi, Ae Rim; Ryu, Seung Wook; Park, Kyung Won; Choi, Ji Hye; Oh, Il Kwon (Applied Surface Science Advances, 2025)
This study investigates the effect of tin (Sn) content on the chemical, structural, and electrical properties of zinc tin oxide (ZTO) thin films. By varying the Sn content in the ZTO films grown via atomic layer deposition (ALD), we analyzed their chemical composition and structural properties using X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD). Analysis of the Sn composition in ZTO films grown by supercycle ALD revealed a higher Sn content than expected based on theoretical predictions. This deviation is examined through in-situ quadrupole mass spectrometer (QMS) monitoring of the diethylzinc (DEZ) ALD reaction byproducts, which indicates variations in reactive site density during the alternating deposition cycles of ZnO and SnO₂. While DEZ adsorption involves a single ethyl ligand exchange, maintaining site density, the tetrakis(dimethylamino)tin (TDMASn) ALD reaction can alter it by changing reactive sites based on dimethylamino (DMA) ligands. The results indicate that increasing the Sn content decreases the number of oxygen vacancies in the films because of the stronger bond strength between Sn and O. Thin-film transistors (TFTs) are fabricated using ZTO films with different Sn compositions, and their electrical properties were evaluated. The results show that increasing the Sn content enhances electron mobility (which reaches a peak value at a specific Sn concentration) and shifts the threshold voltage of the TFTs. These results suggest that controlling Sn content is crucial for optimizing the performance of ZTO-based TFTs.
Keywords: Atomic layer deposition; Oxide semiconductor; Thin film transistor; Zinc-tin-oxide